Toleransi Beragama Dari Sudut Pandang Agama Minoritas - Adib, M. Afiqul; Diyah, Faiqoh Hami; Tsani, Fitri Hishniya; Furqon, Nuzulul (Mafa Press, 2023)
This discussion aims to examine more deeply about religious tolerance from the perspective of minority religions, especially Buddha at the Dhammadipa Arama Monastery, Malang. This is intended to get a complete picture of tolerance. Because most of those who experience intolerance are minorities, so it would be interesting if his perspective on religious tolerance was reviewed. Field research was selected based on various considerations and suggestions from various parties. Data collection was carried out on the spot. This research is included in the qualitative category, or it can be said that this research is comprehensive to understand the environment (such as behavior and phenomena). The results of the study show that even for minorities (especially at the Dhammadipa Arama Monastery), religious harmony is also important to strive for. And one of the practical solutions that can be applied is to improve communication between religions. Because often conflicts occur because of a lack of understanding of each other. then to address various issues one should look at it from several points of view so that one does not arbitrarily conclude with one's own rationality.